Spanien und die Sepharden: Geschichte, Kultur, Literatur - Rehrmann, Norbert (Romania Judaica, 1999)
One writer wrote recently that from the 8th to the 15th century, the Iberian peninsula was a 'locus of encounter' without parallel in the history of the world. Only in Spain did Moors, Jews, and Christians live together relatively peaceably for almost a thousand years. Their cultural achievements were without peer in the rest of Europe and had a major and lasting influence on the Renaissance. After the Jews were driven out of Spain (1492), they made a crucial cultural and economic contribution to their new homes (Amsterdam, Hamburg, Saloniki, etc.). In Spain itself, the history of the Jewish p